Scouts' Perspectives on Learning Experiences from a Pedagogical Innovation Scope - José Sinde; José Matias Alves (MDPI AG, 2024)
The Portuguese educational system aims at nurturing the holistic development of individuals and societal progress, surpassing the mere transmission of curriculum-based knowledge. While considerable advancements have been made, the need for ongoing innovation and equal educational opportunities remains evident, so that all children can have not only equal access to education, but also equal chances of success. This study investigates the largest Portuguese Scout movement, the CNE, exploring its organisational and pedagogical approaches, potentially applicable in formal education settings. This research surveyed participants aged 18-22, having completed approximately 12 years in the Scout movement. Data collection via focus group followed a semi-structured script, before a thorough content analysis was carried. Findings are organised as follows: Pedagogical organisation in learning cycles; Patrol system; The four stages of the Project Method; Characterization of the Scout Game and other learning process dimensions; Other competencies and values developed throughout the Scout learning course; and Comparisons with formal education contexts. The discourse of participants strongly suggests the Scout movement's potential to inspire educational change, displaying consistent indicators of pedagogical innovation. The study advocates for further exploration of the CNE's pedagogical functioning and its potential to serve as an inspiration for transformative changes in educational systems worldwide, as evidenced by the learners' reflections.